2022
DOI: 10.1155/2022/9011259
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Glucocorticoid plus Intravenous Immunoglobulin in Children with Immunoglobulin-Insensitive Kawasaki Disease

Abstract: This study mainly analyzes the clinical effect of glucocorticoid (GC) plus intravenous immunoglobulin (IVIG) in treating children with immunoglobulin (Ig)-insensitive Kawasaki disease (KD). From September 2013 to November 2021, 86 Ig-insensitive KD children were selected, including 46 children (observation group, Obs) treated with GC plus IVIG, and 40 children (control group, Con) treated with IVIG. The symptom (fever and fever) resolution time, inflammatory factors (C-reactive protein, CRP; procalcitonin, PCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A retrospective study compared IVIG and glucocorticoids to IVIG alone. Using outcome measure of fever and rash resolution as well as laboratory markers of inflammation, the study concluded that the combination had a good safety profile while promoting resolution of symptoms and inflammation [42]. A single-site, single-blind randomized clinical trial from Iran compared high-dose intravenous methylprednisolone therapy to IVIG in 40 cases of Kawasaki disease and found no significant differences in coronary artery aneurysm outcomes at 2 months [43].…”
Section: Kawasaki Diseasementioning
confidence: 99%
“…A retrospective study compared IVIG and glucocorticoids to IVIG alone. Using outcome measure of fever and rash resolution as well as laboratory markers of inflammation, the study concluded that the combination had a good safety profile while promoting resolution of symptoms and inflammation [42]. A single-site, single-blind randomized clinical trial from Iran compared high-dose intravenous methylprednisolone therapy to IVIG in 40 cases of Kawasaki disease and found no significant differences in coronary artery aneurysm outcomes at 2 months [43].…”
Section: Kawasaki Diseasementioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%